Quality Management in Education to Enhance Student Independence: A Literature Review - Iis Susanti; Oki Dermawan; Muhammad Anas Maarif (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2026)
The core stages involved in the management framework for early childhood education (ECE) institutions are planning, organizing, implementing, and evaluating. These functions serve as the primary framework for managing educational activities professionally and ensuring continuous improvement in quality professionally. Educational quality management is a pivotal aspect of enhancing quality, as it is believed to be the primary asset in facing competition. Therefore, an educational institution must be managed comprehensively and in an integrated manner. Essentially, quality management is directed toward consistently meeting consumer needs and achieving continuous improvement in every aspect of the institution's activities. Early It emphasizes not only academic success but also the development of traits like independence, which are crucial at this stage.